Lone Heroes and the Myth of the American West in Comic Books, 1945-1962 - Huxley, David (Palgrave Studies in Comics and Graphic Novels, 2018)
This book examines the role of comics in the perpetuation of the myth of the American West. In particular, it looks at the ways in which lone central characters, and their acts of violence, are posited as heroic. In doing so, the book raises questions both about the role of women in a supposedly male space, in addition to the portrayal of Native Americans within the context of this violence. Various adaptations of historical figures, such as Buffalo Bill and Billy the Kid, as well as film and television stars such as The Lone Ranger and Dale Evans are examined in detail. Although concentrating on American comics, examples both from Britain and France are also analyzed.